Pengaruh Lingkungan Kerja, Kepuasan Kerja dan Budaya Kerja dalam Meningkatkan Kinerja Karyawan UMKM Pukis Bikang Rahayumas Surabaya - Erwansyah, Dony; Nugroho, Riyadi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to identify and analyze the influence of the work environment, job satisfaction, and work culture on employee performance at UMKM Pukis Bikang Rahayumas Surabaya. The research employs a quantitative approach with a causal associative design to examine the relationships between variables. Data were collected through questionnaires distributed to all employees of UMKM Pukis Bikang Rahayumas Surabaya, resulting in 53 respondents. The reliability test results indicated that all research instruments were reliable, with Cronbach’s Alpha values exceeding 0.60. Meanwhile, the validity test results showed that all indicators were valid, as the calculated r-values were greater than the r-table values.Classical assumption testing confirmed that the data met the required assumptions, including normal data distribution, no multicollinearity, and no heteroscedasticity. Hypothesis testing was performed using partial tests (t-tests) and a simultaneous test (F-test). The t-test results revealed that the work environment, job satisfaction, and work culture each have a positive and significant effect on employee performance. In addition, the F-test results demonstrated that these three variables simultaneously have a significant influence on employee performance.Overall, the findings indicate that a supportive work environment, high job satisfaction, and a positive work culture are essential factors in improving employee performance at UMKM Pukis Bikang Rahayumas Surabaya. These results highlight the importance of effective human resource management in enhancing performance within micro, small, and medium enterprises.